2003
DOI: 10.18785/goms.2102.01
|View full text |Cite
|
Sign up to set email alerts
|

Meristic and Morphometric Differences in Populations of Rivulus marmoratus

Abstract: Rivulus marmoratus (Pisces: Aplocheilidae) is a small cyprinodontid found in mangroves of the western tropical Atlantic and is the only lmown self-fertilizing, hermaphroditic vertebrate. Populations normally consist of genetically diverse groups of homozygous clones. Rivulus marmorahts has the widest range of any member of the genus (southern Brazil to central Florida) and is the only marine representative of the genus. There has been considerable speculation about the "origin" of the species in an otherwise s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The much larger genetic distances between versus within K. marmoratus and K. ocellatus are also obvious in a mitochondrial phylogeny in which individual fish are treated as units of analysis (Fig. 2), and they are consistent with separate-species status for these two taxa (24). A qualitatively similar pattern of relationships is apparent in a microsatellite phenogram of populations (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…The much larger genetic distances between versus within K. marmoratus and K. ocellatus are also obvious in a mitochondrial phylogeny in which individual fish are treated as units of analysis (Fig. 2), and they are consistent with separate-species status for these two taxa (24). A qualitatively similar pattern of relationships is apparent in a microsatellite phenogram of populations (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Our surveys resulted in samples covering most of the geographic distribution of the K. marmoratus species complex, including several geographic areas where these species have not previously been reported. Identification of species in the K. marmoratus complex is difficult using morphological characters (Taylor, 2003), but the three valid species of the complex (K. ocellatus, K. hermaphroditus and K. marmoratus) are easily distinguishable with genetic markers such as microsatellites or mitochondrial DNA (mtDNA) (Tatarenkov et al, 2009(Tatarenkov et al, , 2011. Therefore, instead of trying to fit our collections into a particular species based on morphology, we chose to first determine major genetic groupings of the selfing mangrove rivulus and only then evaluate how these groups agree with current taxonomy.…”
Section: Introductionmentioning
confidence: 99%
“…Lin and Dunson (1995) showed genotype effects on egg volume and hatchling size, Edenbrow and Croft (2011) revealed genotypic effects on age at maturity and on the total number of eggs laid between 105 and 151 days posthatching, and Grageda et al (2005) described genotypic effects on fecundity and growth rates (0-100 days posthatching). Conclusions about genotypelevel differences in life history, behavior, and physiology seem contingent upon the number and identity of the genotypes compared; for instance, Grageda et al (2005) showed minimal differences in morphological characters between Panamanian and Belizean lineages, contrasting Taylor's (2003) evidence for marked differences in a similar set of characters among populations/genotypes derived from various locations in Florida, Belize, Honduras, Bahamas, and Brazil. We should therefore, expand the number of genotypes used in our studies, and perhaps select many genotypes from each of a number of populations that span the fish's geographic range (e.g., Edenbrow and Croft 2011).…”
Section: Evidence For Genetic Variance Underlying Phenotypic Diversitymentioning
confidence: 99%